Pakan banyu (Croton argyratus Blume) stembark ethanol extract effectiveness to total spermatogenic cells of white male rats (Rattus norvegicus) - Noor cahaya; M. Aditya Sholihin; Nurlely Nurlely (Universitas Ahmad Dahlan, 2017)
Stembark of Pakan Banyu (Croton argyratus Blume) empirically used as traditional contraception. The stembark contained active substances as steroids, saponins and alkaloids tannins alleged antifertillity for men. The purpose of this study was to demonstrate the potential of Pakan Banyu stembark ethanol extract to the total number of spermatogonium cells, primary spermatocytes, spermatids and spermatozoa in male rats. This study was an experimental research design posttest only control group design using 20 male rats into 4 groups of 5 mice. The control rats were used in treatment group, the rats were given the pakan banyu stembark extract at a dose of 100, 200 and 500 mg / kg with 0.5% CMC Na suspending agent. The treatment was given orally for 15 days at the 16th days surgery was done to the testicles organs, then microanatomy preparations were made using paraffin method and using HE colour. Analysis of data using One-way ANOVA and Kruskal Wallis with 95% confidence level. The results showed that there is no effect of Pakan Banyu stembark ethanol extract against spermatogonium cells, primary spermatocytes, spermatids and spermatozoa.Â